2011
DOI: 10.2991/ijcis.2011.4.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Design of 2-D Recursive Filters Using Self-adaptive Mutation Differential Evolution Algorithm

Abstract: This paper investigates a novel approach to the design of two-dimensional recursive digital filters using differential evolution (DE) algorithm. The design task is reformulated as a constrained minimization problem and is solved by an Self-adaptive Mutation DE algorithm (SAMDE), which adopts an adaptive mutation operator that combines with the advantages of the DE/rand/1/bin strategy and the DE/best/2/bin strategy. As a result, its convergence performance is improved greatly. Numerical experiment results confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The mutation operator based on "best" takes the parameter vector with best fitness in the contemporary population as a base vector, which has good local exploitation ability and fast convergence rate, but easy to fall into local optimal solution, causing search stagnation and premature convergence. Considering the advantages of two mutation operators, a new self-adaptive mutation operator is proposed based on Wu et al 21 The mutation operator is shown in equation ( 17)…”
Section: Self-adaptive Mutation Differential Evolution Constrained Optimization Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation operator based on "best" takes the parameter vector with best fitness in the contemporary population as a base vector, which has good local exploitation ability and fast convergence rate, but easy to fall into local optimal solution, causing search stagnation and premature convergence. Considering the advantages of two mutation operators, a new self-adaptive mutation operator is proposed based on Wu et al 21 The mutation operator is shown in equation ( 17)…”
Section: Self-adaptive Mutation Differential Evolution Constrained Optimization Algorithmmentioning
confidence: 99%
“…where p 1 and p 2 represent weighting factors of position constraint and orientation constraint, respectively, to normalize the corresponding values in equation (21). We propose to choose p 1 and p 2 suggested in Tabandeh et al 8 as shown in equations ( 22) and ( 23)…”
Section: Is Outlined Asmentioning
confidence: 99%
“…Video signal processing contains 3-D digital signals and their applications (Bovik 2005). Multidimensional signal processing deals with two, three and more dimensional digital signals (Dudgeon and Mersereau 1983;Woods 2006).…”
Section: Introductionmentioning
confidence: 99%